Plus Ça Change: The Persistence of ‘Skill Talk’ in Competency Discourse - Ruitenberg, Claudia W. (Philosophical Inquiry in Education, 2019)
Robin Barrow has critiqued the use of the concept of “skill” for a wide range of human attributes that are not skills in the precise sense he articulated, namely: “a capacity that is discrete and can be perfected through practice and exercise.” Skill talk has persisted, though today commonly under the guise of “competency discourse.” In recent years, the British Columbia Ministry of Education has implemented a new K-12 curriculum that relies heavily on “communication competency,” “thinking competency” and “personal and social competency.” Based on Barrow’s work, I critique the tendency to refer to a wide range of human qualities as “competencies.” In addition, I argue that competency discourse commits a category mistake, especially with respect to moral qualities in the “personal and social competency” domain. After taking a closer look at the area of “personal and social competency” in BC’s new curriculum, I discuss the concept of friendship as an example of an area of significance to human life that cannot be reduced to competency. I close the paper by discussing why it matters that competency discourse commits a category mistake, and why philosophers of education should resist competency discourse.